Needlestick Injury Risk and Preventive Behaviors among Nursing Students - Wilandika, Angga; Alfin, Riandi; Khoerunnisa, Rosa Intan (Makara Journal of Health Research, 2026)
Background: Needlestick injury (NSI) remains a persistent occupational safety risk for nursing students during clinical practice, with implications for worker safety, patient care, and healthcare safety systems. Understanding preventive safety behavior within clinical training environments is essential for improving workplace safety in healthcare settings. Methods: A cross-sectional study was conducted among nursing students undertaking hospital-based clinical placements. Using a purposive sampling, participants completed a structured self-administered questionnaire assessing NSI exposure, preventive safety behaviors, clinical supervision, safety training, and perceived safety within the clinical learning environment. Data was analyzed to identify patterns of NSI risk and associated preventive behaviors. Results: NSI exposure during clinical practice was frequently reported, with variability in adherence to preventive safety behaviors. Preventive behaviors were associated with the quality of clinical supervision, participation in safety training, and the perceived safety climate. Gaps between expected safety standards and actual clinical practices indicated weaknesses in workplace safety systems. Conclusion: NSI risk among nursing students is influenced by both individual behavior and organizational safety conditions. Strengthening supervision, safety training, and safety-oriented clinical systems is essential to promote consistent preventive practices and improve occupational safety during clinical education.